The role of thermal energy communities in Germany's heating transition - Hartmann, Katharina; Palm, Jenny (Frontiers in Sustainable Cities, 2023)
A rapid decarbonization of the energy sector is key for mitigating climate change and in this transformation a transition to renewable heating is essential. To date, most attention in both research and policy on decarbonization has been on electricity and transport systems, with less interest in the heating system. Half of the EU's final energy consumption is made up by the heating and cooling sector, making this an important sector for reducing fossil fuel consumption. This article addresses the lack of research on decarbonization of heating by answering the question, what barriers and drivers do Thermal Energy Communities (TECs) perceive when trying to enter the market and play a role in the decarbonization of heating in Germany? Eight TECs and four umbrella organizations in Germany have been interviewed about their experiences of initiating and running a TEC. The results show, amongst others, that the political support of municipalities is put forward as an essential driver and important factor for success. However, barriers for municipalities to get involved were often that they lacked expertise, capacity and financial resources. An important driver for TECs was the involvement of local experts and professionals who could support the volunteers often in charge of a TEC. The results show that TECs that included professionals had an advantage in building heating systems, as they could better address their complexity and high initial costs. Another prevalent result was the need for community engagement and citizen mobilization, which is a greater need in heating projects compared to those focusing on electricity, due to community heating systems requiring a substantial number of customers for profitability.